Increased availability and quality of water for communities in Ujung Kerang, Nelayan village, Medan Belawan (Talenta Publisher, 2019)
One of the goals of the Sustainable Development Goals (SDGs) is to ensure the availability and management of sustainable water and sanitation for all. In general, the supply of clean water to the community is supplied by local government-owned water companies. However, due to network limitations or production capacity often not all people can enjoy the clean water facilities, especially the poor who live on the outskirts or outside the city. The dominant coastal area inhabited by fishing villages is identical to slums. These slums are visible in scattered rubbish, unhealthy latrines and inadequate quality and quantity of clean water. Ujung Kerang Village, Seberang Fishing Village, Medan Belawan District has a problem related to water availability, which is the unequal distribution of clean water and the quality of water that is physically turbid and tasteless. Clean water is needed in meeting the daily needs of the fishing communities to drink, wash and bathe. The limitations of the source and distribution of clean water so that the fishing village community must travel a long way to get clean water and must pay dearly to get clean water. Because of the coastal area so that the depth of a wellbore that can produce clean water quality on average must be> 50 m so that the cost of making the wellbore is expensive. Based on these problems, the solution given is to make a wellbore with a depth of Â± 100 m. This well is equipped with a suction pump and pressure tank. This drill well can be utilized by Â± 10 households by making a self-supporting distribution pipeline to their respective homes. Operational and maintenance costs will be borne by the people who use the wellbore water.